2009
DOI: 10.1080/00016350902758607
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of demarcated opacities and their sequelae in permanent 1st molars and incisors in 7 to 13-year-old Brazilian children

Abstract: A high prevalence of demarcated opacities, possibly resulting in disintegration of the tooth crown, has been found in Brazilian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
116
5
16

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(167 citation statements)
references
References 15 publications
16
116
5
16
Order By: Relevance
“…Weeheijm et al [3] characterized the hypomineralization as a demarcated opacity, not diffuse. Some authors, however, modified the definition of hypomineralization to include other clinical criteria such as "color changes or ill structuring" or changing the word "systemic origin" into developmental, qualitative, morphological, or asymmetrical [10, 13,[18][19][20]. Some authors also included other teeth such as the permanent canines, permanent second molars, or primary teeth in the definition [19,21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weeheijm et al [3] characterized the hypomineralization as a demarcated opacity, not diffuse. Some authors, however, modified the definition of hypomineralization to include other clinical criteria such as "color changes or ill structuring" or changing the word "systemic origin" into developmental, qualitative, morphological, or asymmetrical [10, 13,[18][19][20]. Some authors also included other teeth such as the permanent canines, permanent second molars, or primary teeth in the definition [19,21].…”
Section: Resultsmentioning
confidence: 99%
“…Lygidakis et al [25] and Kevrekidou et al [20] suggested that it's better to classify MIH cases into two groups only (mild and severe) combining the previously designed two categories of moderate and severe into one group. Some investigators [13,26] based their data only on a classification of 0 and 1, where 0 indicates sound teeth or a normal dentition while 1 denotes MIH affected case without reporting grading or severity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No Brasil, os dados de reconhecimento desta patologia, bem como de sua prevalência na população, ainda são poucos (6,7,8,9), mas o seu conhecimento aprofundado, com identificação precisa de sua etiologia, mostra-se relevante. Uma possível consequência de um esmalte defeituoso, por exemplo, é um rápido desenvolvimento de lesões de cárie, logo após a erupção dos molares permanentes, com necessidade de procedimentos clínicos e tratamentos recorrentes.…”
Section: Introductionunclassified
“…A falta de acompanhamento médico durante a gestação mostrou porcentagem elevada, mas sem valor estatístico; dos indivíduos pesquisados que possuíam MIH (N=9), 22,22% informaram não ter feito pré-natal (p-valor 0,19; OR:3). Em relação a idade gestacional 11,11% das crianças com MIH eram prematuras (2)(3)(4)(5)(6)(7)(8)(9)14). Das crianças com MIH, 66,7% mamaram no seio materno mais do que 1 ano, (p-valor=0,05) (95% de confiança) mostrando uma relação estatisticamente significativa.…”
unclassified